Testing the validity and reliability of the Chinese version of the Staden schizophrenia anxiety rating scale - Du, Chenyuan; Chen, Jiayue; Ma, Xiaoyan; Tu, Wenzhen; Chen, Langlang; Liu, Jian; Zhou, Dan; Chen, Xinying; Zhang, Jiulong; Tian, Hongjun; Zhuo, Chuanjun; Jiang, Deguo (Frontiers in Psychiatry, 2022)
Abstract Accurate assessment of anxiety disorders and their symptomatology in schizophrenic patients is important for prognosis and treatment. Measuring anxiety on the traditional anxiety assessment scales such as the Hamilton Anxiety Rating (HAMA) Scale or the self-rating depression scale (SAS) is challenging and often considered unsuitable for assessing anxiety symptoms in patients with schizophrenia. The Staden schizophrenia anxiety rating scale (S-SARS) has been shown to reliably measure specified and undifferentiated anxiety in schizophrenia. The present study aims to test the reliability and validity of the S-SARS version, thereby facilitating Chinese psychiatrists in assessing anxiety symptoms in schizophrenic patients. A total of 300 patients meeting ICD-10 diagnostic criteria of schizophrenia were recruited by convenience sampling. We used the exploratory factor analysis (EFA) to evaluate the structural validity of S-SARS and receiver operating characteristic (ROC) curves to acquire the cutoff point of S-SARS to define the severity of anxiety. Internal consistency was assessed using Cronbach's and Krippendorff’s α scores. One-week test-retest reliability was assessed using the intra-class correlation coefficient (ICC). Correlation analysis with HAMA was used to determine the Chinese version of S-SARS criterion validity. We have the following results: Our version of S-SARS showed Cronbach's α score as 0.899, Krippendorff’s α as 0.874, and a correlation coefficient of 0.852 between S-SARS and HAMA. The EPA demonstrated that the contribution rate of major factors was 69.45%. All the items of S-SARS were located in one factor and showed a high factor load (0.415~0.837). The correlation coefficient of S-SARS and HAMA was 0.852. Our results indicated that Chinese version of S-SARS showed good constructive validity and reliability. It also showed better criterion validity compared to HAMA. The S-SARS and its Chinese version can thus serve as an effective tool for assessing anxiety symptoms in patients with schizophrenia.